2011
DOI: 10.1038/sc.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to sexual activity: counselling spinal cord injured women in Malaysia

Abstract: Study design: This study is a cross-sectional, face-to-face interview. Objectives: To examine the sexual activity in a sample of Malaysian women with traumatic spinal cord injuries (SCIs), identify the physical and psychological barriers to it, and explore their experiences with sexual counseling and rehabilitation. Setting: This study was conducted at the Spinal Rehabilitation Unit of a teaching hospital. Methods: All women who attended scheduled check-ups, over 1 year, and who met the inclusion criteria (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…6,7 However, to our knowledge, no previous formal academic study has described the overall current state of sexuality and sexual satisfaction among Asian men with motor complete SCI. In the present study, 62.7% of the participants were SA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However, to our knowledge, no previous formal academic study has described the overall current state of sexuality and sexual satisfaction among Asian men with motor complete SCI. In the present study, 62.7% of the participants were SA.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, despite this impact, the sexual activity of individuals with SCI has largely been neglected as a focus of research and is one of the most unmet needs for this group of individuals. 4,5 In particular, although the sexual activity and coping strategies of people with SCI will likely be diverse across cultures because of cultural differences, 6,7 little research has been published regarding the sexuality of individuals with SCI, particularly in East Asia. In one of the few studies addressing this issue for an Asian population, a comparative investigation of the life satisfaction between long-term survivors of SCI in Sweden and Japan found that the percentage of sexually active (SA) males engaged in sexual intercourse was significantly lower in Japan than in Sweden, and also observed an absence of sexual counseling for disabled people in the former country.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that 60–70% of SCI patients desired sexual relations (10); however, in China, patients remained reluctant to discuss their sexual health issues due to cultural traditions. As a consequence of this cultural taboo, a full assessment of erectile issues was not completed; however, the information from the limited number of individual SCI patients willing to discuss this subject was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…The related factors that we found in our study are not having a stable partner and the lack of sensation in the genital area, results that agree with the literature published to date. 6,10 Important factors in SCIs, such as the neurological level, ASIA or SCIM scores, age, time since SCI, urinary incontinence, chronic pain and spasticity, were not found to be related to sexual satisfaction.…”
Section: Sexual Satisfaction In Spinal Cord Injuries S Otero-villavermentioning
confidence: 99%
“…4,5 In contrast, their sexuality undergoes changes due to urinary or intestinal incontinence, spasticity, pain or difficulty maintaining social relations, 6 which frequently lead to a reduced desire for 7 and frequency of sexual relations. 8 It is worth emphasizing that in recent years more studies on sexual disorders in women with SCIs have emerged, although the literature remains highly limited on this topic.…”
Section: Introductionmentioning
confidence: 99%